Between leading and lagging: Interregional migration, unemployment and over-education among college graduates in the aftermath of the 2008 recession - González-Leonardo, Miguel (REGION, 2023)
In this paper, we analyse the interregional migration of Spanish-born young adults by educational attainment and explore unemployment and over-education in the labour market among internal migrants and sedentary individuals with a university degree. We used register data of population movements from 2000 to 2018 to analyse internal migration patterns and the Labour Force Survey to study the educational attainment of migrants, as well as unemployment rates and over-education among college graduates. Our results indicate a regional polarisation after the economic crisis. Peripheral regions in the interior of Spain have been affected by an increasing exodus of university graduates, in addition to high levels of unemployment and over-education among individuals with a university degree who remain at origin. However, peripheral regions in the north-west and south of Spain have been less affected by out-migration, even though the south has shown higher levels of unemployment for college graduates. The central region of Madrid has emerged as the main destination for university graduates, with a large capacity to employ populations with university education from other regions. Semi-central regions of the Mediterranean and north-east of Spain retain local college graduates and exhibit good labour market conditions among residents with a university degree, but they are not destinations of individuals with university education from other regions.